Health-Related Quality of Life among Persons Living with Buruli Ulcer in Amasaman Community, Ga West District Accra, Ghana - HAMZAT, Talhatu K.; BOAKYE-AFRAM, Bernard (International Journal of Health Sciences, 2011)
Objectives: This cross-sectional study compared the health-related quality of life (HRQoL) of individuals with Buruli ulcer (Focus group) and age-matched apparently healthy peers without the ulcer (Control group) living in Amasaman in the Ga West District, Ghana. Gender pattern in the Health-Related Quality of Life of the Focus group was also investigated. Methodology: Participants comprised of consecutively recruited 84 Focus and 100 Control group subjects. Socio-demographics of all participants and the clinical profile of Focus group subjects were obtained. The Nottingham Health Profile Questionnaire was used to measure the quality of life. Data was analysed using Mann-Whitney U statistic at 0.05 alpha. Results: Focus group had significantly higher scores than Control in all the six (6) domains of the Nottingham Health Profile (p<0.05); no significant difference was observed in the total health score of females compared to males in both the Focus and Control groups (p>0.05). Conclusion: The findings suggest that, Buruli Ulcer impact negatively on the Health-Related Quality of Life of the victims. Aside medical interventions, the quality of life as well as the socio-cultural and economic impacts of Buruli ulcer should be taken in cognizance while planning community-based rehabilitation programmes for those affected. Keywords: Buruli Ulcer; Health-Related; Quality of Life